Review of Modeling and Simulation Methods for Cyber Physical Power System - Fan, Hong; Wang, Hongxiang; Xia, Shiwei; Li, Xuan; Xu, Pengfei; Gao, Yuhan (Frontiers in Energy Research, 2021)
With the development of informatization and intellectualization technology, the power system has become the cyber-physical power system (CPPS) with deep integration of the cyber side and the physical side. As the support system of smart grids with new forms and features, the CPPS considers the coupling relationship between the communication network and the physical power grid, and is a research hotspot in the field of smart grids. This paper provides an overview of the CPPS framework and describes the interaction between the communication network and the physical power grid. Then the mainstream modeling and simulation methods of CPPS are summarized, and the advantages and disadvantages of each method are pointed out. In the end, the paper looks forward to the possible research directions of CPPS in the future. The article provides researchers with different perspectives on the dynamic model and simulation methods of CPPS.